2013
DOI: 10.1186/1471-2156-14-106
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genomic analysis of domestic and wild pig populations from the Iberian Peninsula

Abstract: BackgroundInbreeding is among the major concerns in management of local livestock populations. The effective population size of these populations tends to be small, which enhances the risk of fitness reduction and extinction. High-density SNP data make it possible to undertake novel approaches in conservation genetics of endangered breeds and wild populations.A total of 97 representative samples of domestic and wild pig populations from the Iberian Peninsula, subjected to different levels of threat with extinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 61 publications
(116 reference statements)
5
95
1
3
Order By: Relevance
“…Landrace and Yorkshire presented a higher proportion of longer ROH segments compared to the other populations, suggesting higher levels of recent inbreeding in these breeds and thus lower individual genetic diversity. A characterization of ROH in pigs has also been previously reported by Herrero-Medrano et al [35] for pig populations from the Iberian Peninsula. The authors reported a mean of the total number of ROH per population between 24 and 34, which are slightly higher than the values reported in the present study, however, consistent with the breeds’ history.…”
Section: Discussionsupporting
confidence: 63%
“…Landrace and Yorkshire presented a higher proportion of longer ROH segments compared to the other populations, suggesting higher levels of recent inbreeding in these breeds and thus lower individual genetic diversity. A characterization of ROH in pigs has also been previously reported by Herrero-Medrano et al [35] for pig populations from the Iberian Peninsula. The authors reported a mean of the total number of ROH per population between 24 and 34, which are slightly higher than the values reported in the present study, however, consistent with the breeds’ history.…”
Section: Discussionsupporting
confidence: 63%
“…However, in some studies (e.g. Herrero-Viedma et al, 2013) N e (LD) have large standard errors and are also sensitive to assumptions of constant N e (Corbin et al, 2012). Suggesting that the assumptions of the Wright equation are sometimes met in actual populations, Harmegnies et al (2006) found that in two commercial pig populations (each maintained at about ten boars and 250 to 300 sows) N e (LD) agreed 'reasonably well' with N e (Wright).…”
Section: Discussionmentioning
confidence: 75%
“…The white phenotype of the Rongchang pig is a recessive trait (Lai et al, 2007) and there is high conservation-related interest in investigating the origin of the PW breed. Knowledge of the genetic structure, based on genomic data, has been important in revealing the demographic and evolutionary history of pig breeds worldwide (Ai et al, 2013;Herrero-Medrano et al, 2013;Pham et al, 2014;Traspov et al, 2016). However, to date, the genetic structure of PW has scarcely been investigated, despite the specific, desirable qualities of this breed, including high prolificacy, high meat quality and good adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers, particularly SNPs, are widely used to explore important questions in population genetics and domestication. High-density SNP analysis plays an essential role in revealing the past and current population demographics (Herrero-Medrano et al, 2013). In our study, highquality reads (removing primer/adaptor contaminated reads) with average base quality scores ⩾20 (indicating an error rate of base calling of 1 in 100) were used to call SNPs, and the average sequencing depth for SNP calling was 16.3×, providing high confidence in the identified variants.…”
Section: Discussionmentioning
confidence: 99%